Digital Hermeneutics and Religious Authority in the ChatGPT Era: Murtadha Muthahhari’s Perspective - Lilik Riandita; Muliadi Muliadi; Luluk Maktumah (Social Science Academic, 2026)
Generative artificial intelligence has changed how people access, interpret, and evaluate religious information. This article examines the transformation of religious authority in the ChatGPT era through digital hermeneutics and Murtadha Muthahhari’s epistemological perspective. The study uses qualitative library research with an interpretive-philosophical approach. Primary sources are selected works by Muthahhari, while secondary sources address digital religion, algorithmic mediation, large language models, AI ethics, and contemporary debates on religious authority. ChatGPT outputs are treated as secondary interpretive material, not as authoritative religious sources. The analysis finds that AI produces three interconnected shifts: wider access to religious information, more dialogical and personalized interpretation, and a growing risk that fluency and accessibility will be mistaken for authority. From Muthahhari’s perspective, information processing cannot be equated with religious knowledge because reason, revelation, experience, moral responsibility, and spiritual formation are interconnected. ChatGPT can therefore serve as an epistemic and interpretive aid, but not as an autonomous religious authority. The article proposes a human-in-the-loop model of digital religious literacy in which AI supports exploration and learning, while qualified scholars and users remain responsible for verification, contextual interpretation, normative judgment, and ethical consequences.